INTERAKSI KEMAMPUAN AWAL MATEMATIS SISWA DAN PEMBELAJARAN DENGAN STRATEGI ABDUKTIF-DEDUKTIF TERHADAP PENINGKATAN KEMAMPUAN PENALARAN DAN DISPOSISI MATEMATIS SISWA - Ali Shodikin (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2015)
Reasoning ability and mathematical disposition are cognitive and affective abilities which require impovements. This study aims to examine the interaction between students’ early mathematical ability and instructions in improving their reasoning ability and mathematical disposition. This research implemented abductive-deductive strategy and expository learning at the 11th grade classes of a state senior high school in Pati regency, Central Java, Indonesia. The researcher carried out a nonrandomized experimental-control group with pretest-posttest design. Quantitative analysis based on early mathematical ability (high, medium, low) was used to analyze the data. The results showed that the interaction between early mathematical ability and learning gave significant impact in improving the students’ reasoning ability. However, the interaction between early mathematical ability and learning gave no significant impact in improving the students’ mathematical disposition. These findings indicated that in learning, especially in improving reasoning ability, students’ early mathematical ability need to be considered. Yet, to improve mathematical disposition, students’ early mathematical ability gave no significant effect thus further studies to find out the influence of other factors need to be done.